2014
DOI: 10.15376/biores.9.4.6707-6718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ammoniation Pretreatment at Low Moisture Content on Anaerobic Digestion Performance of Rice Straw

Abstract: The effect of ammonia pretreatment on the anaerobic digestion performance of rice straw was investigated. The rice straw was pretreated with four different moisture contents (30%, 50%, 70%, and 90%) and three concentrations of ammonia (2%, 4%, and 6%). The results showed that the anaerobic digestion achieved best performance for the rice straw pretreated by ammonia concentration of 4% and moisture content of 70%, and biogas yield achieved the highest value (396.92 mL·g -1 total solid), which was 21.9% higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The R3 group, with 77% moisture content during pretreatment, obtained the highest methane yield, but its yield was not significantly higher than those of the R1 and R2 groups. An increase in biogas yield with the increment of moisture content was also observed in the ammonia pretreatment of rice straw with 2% ammonia content (w/w) (Yuan et al 2014). This phenomenon was ascribed to the increase in the alkali transfer rate and reaction extent, thereby resulting in a greater disruption of lignocellulosic structure, thus improving the digestibility of lignocellulosic biomass (Liang et al 2011;Yuan et al 2014).…”
Section: Moisture Content Influence On Biogas Production By Bmp Testmentioning
confidence: 83%
See 2 more Smart Citations
“…The R3 group, with 77% moisture content during pretreatment, obtained the highest methane yield, but its yield was not significantly higher than those of the R1 and R2 groups. An increase in biogas yield with the increment of moisture content was also observed in the ammonia pretreatment of rice straw with 2% ammonia content (w/w) (Yuan et al 2014). This phenomenon was ascribed to the increase in the alkali transfer rate and reaction extent, thereby resulting in a greater disruption of lignocellulosic structure, thus improving the digestibility of lignocellulosic biomass (Liang et al 2011;Yuan et al 2014).…”
Section: Moisture Content Influence On Biogas Production By Bmp Testmentioning
confidence: 83%
“…Thus, Liang et al (2016) reported that 4% NaOH-treated rose stalk produced 44% higher yields than non-NaOH-treated biomass. The moisture content of pretreatment has a remarkable influence on pretreatment performance (Yuan et al 2014;Peces et al 2015). Moreover, the disruption of lignocellulosic structure and removal of chemical composition were affected by the moisture content during pretreatment, thereby changing the biogas production and process stability for anaerobic digestion of pretreated biomass (Yuan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are contrasting reports on the effect of chemical pretreatment techniques on the rate of feedstock hydrolysis during AD process. Yuan et al (2014) and Li et al (2015) have reported that the chemical pretreatment technique is a fast process, while Kumar and Sharma (2017), Gumisiriza et al (2017) and Amin et al (2017) reported that the technique is a slow process. This difference could be due to variations in their chemical pretreatment conditions.…”
Section: Hydrolysis Ratementioning
confidence: 99%
“…Conversely, co-digestion can significantly improve gas production rates due to its advantages of balancing nutrients, diluting toxic substances, and improving microbial activity [14]. Hairong Yuan et al [15] explored the performance of the anaerobic co-digestion of sludge and wheat straw. The results of the study showed that the anaerobic digestion performance of sludge was affected by different C/N ratios, and the use of anaerobic co-digestion resulted in higher gas production than single sludge.…”
Section: Introductionmentioning
confidence: 99%